Effect of in-service aircraft mission variation on airline fleet management - Chen, Han Hua (Cranfield University, 1996)
The air transport markets affected by global economic climate and regional demand characteristics are evolving fairly dynamically. To cope with the evolving demand and to penetrate desired market segments, operators' usage of aircraft has been getting more and more dynamic with increased deviation from the originally designed mission objectives. The objective of this research is to investigate the effects of in-service rrusslon variation on aircraft structural performance so as to provide airlines with a more realistic approach toward better fleet management. During the research, the scenarios and phenomena causing fleet in-service mission variations were investigated. A survey on the utilisation of world-wide aircraft fleets was conducted and presented. The in-service missions of aircraft fleets were found to vary significantly in terms of mission profile. Furthermore, the utilisation patterns of individual aircraft in the same fleet of a major airline are also being thoroughly analysed. Tremendous variations of mission mixes are found among individual aircraft. In order to analyse the effects of the in-service mission variation, methodologies and models based on fatigue test results have been developed by the author. Actual service data are being input for the effect analysis. It is found that the mission variation has a considerable engineering influence on the aircraft's structural performance either in terms of mission airworthiness or fatigue life span. Finally, a conceptual model, the 'Integrated Airline Fleet Management Model' (IAFM), has been developed as a blueprint for practical application. By implementing the IAFM, airline will be able to obtain a realistic picture of the health of its aircraft. With a more reliable basis for maintenance planning, improved inspection accuracy, reduced maintenance cost and better structural airworthiness can be achieved.